Strain induced incommensurate structures in vicinity of reconstructive phase transitions. (1st September 2015) - Korzhenevskii, A L; Dmitriev, V
Abstract: General conditions controlling the formation of incommensurate phases in crystals undergoing reconstructive phase transitions are analyzed in the framework of a model-free phenomenological approach. A universal trend to stabilizing such intermediate phases in the vicinity of reconstructive phase transitions stems from the fact that certain high-order improper Lifshitz invariants reduce at such transformations to ones bi-linearly coupling critical displacement gradients and strains or even to the proper Lifshitz invariant. The approach developed here introduces a universal mechanism for the formation both of premartensite incommensurate phases and complex structures with giant unit cells, as found in some elemental crystals at high pressure.